Mixed heavy metals exposure affects the renal function mediated by 8-OHG: A cross-sectional study in rural residents of China. (15th January 2023) - Tian, Xiaoyu; Shan, Xiaobing; Ma, Li; Zhang, Chenyang; Wang, Mei; Zheng, Jie; Lei, Ruoyi; He, Li; Yan, Jun; Li, Xun; Bai, Yanjun; Hu, Keqin; et al.
Abstract: Heavy metals are important risk factors for kidney, but their co-exposure effect on kidney and related mechanism remain unclear. This study evaluated the relationship between heavy metals and renal function, and the feasible mediation effect of oxidative stress. Based on the Dongdagou-Xinglong cohort, participants were recruited and their information were collected through questionnaires and physical examinations. The urine concentration of heavy metals like Cobalt, Nickel, Molybdenum, Cadmium, Antimony, Copper, Zinc, Mercury, Lead, Manganese, and renal injury biomarkers like β2-microglobulin, β-N-Acetylglucosaminidase, retinol-binding protein, 8-hydroxyguanine (8-OHG) were measured and corrected by creatinine. Linear regression was conducted to analyze the relationship between metals and renal biomarkers. Bayesian kernel machine regression, weighted quantile sum and quantile-based g-computation were applied to analyze the association between metal mixtures and renal biomarkers. Finally, the mediating effect of 8-OHG was analyzed through the mediation model. We found that these metals were positively related with renal biomarkers, where copper showed the strongest relationship. The co-exposure models showed that renal biomarkers increased with the concentration of mixtures, particularly for cadmium, copper, mercury, manganese. In addition, the proportion of 8-OHG in mediating effect of metals on renal function ranged from 2.6% to 86.9%. Accordingly, the renal function damage is positively associated with metals, and 8-OHG may play an important mediating role. Graphical abstract: Image 1 Highlights: Heavy metals is positively associated with renal function impairment either single or co-exposed. Cd, Cu, Hg and Mn may be the key risk factors for renal damage. 8-OHG plays a key mediating role in the process of renal function damage caused by heavy metals.